ANALISIS EFEKTIVITAS APLIKASI BIBIT DALAM MENINGKATKAN LITERASI KEUANGAN MASYARAKAT KOTA PALEMBANG MENGGUNAKAN METODE UTAUT - Priansyah, Erik; Kristina Sipayung, Agnes; Sutabri, Tata (Universitas Majalengka, 2024)
The research investigates the influence of the Bibit Application on financial literacy among residents in Palembang, employing the Unified Theory of Acceptance and Use of Technology (UTAUT) framework. The findings reveal a notable improvement in users' financial understanding, with significant advancements in comprehending financial concepts, managing investments, and planning finances. The study identifies that variables such as age, educational background, and prior investment experience play a crucial role in the enhancement of financial literacy. Based on these insights, the research suggests several recommendations to further augment financial literacy through the Bibit Application. These include the integration of structured educational content within the app, providing targeted user training programs, and establishing partnerships with financial and educational institutions. The overarching aim of the study is to make a substantial contribution to the improvement of financial literacy through the application of financial technology in Palembang. By addressing the specific needs and characteristics of the user base, the study aspires to facilitate a more financially literate society capable of making informed financial decisions..